Requirements for Application for Cancellation of Peace and Analysis of Decision Concerning Cancellation of Peace - Firdaus, Gilbert; Sulistianingsih, Dewi; Pujiono, Pujiono (Universitas Muhammadiyah Malang, 2023)
This writing intends to examine the judge’s ruling on the terms of the peace annulment application. The key focus and main objective of the Suspension of Debt Payment Obligations revolves around the Settlement process, aiming to achieve a peace proposal in accordance with Article 281 of the Bankruptcy and Postponement of Debt Payment Obligations Law, commonly referred to as Law Number 37 of 2004. This occurs within the framework of the Commercial Court's management of the Suspension of Debt Payment Obligations case. If the debtor fails to keep their promise or fulfill the terms of the peace agreement, there is a legal solution to request the annulment of the peace. This research employs a normative juridical method with a descriptive-analytical approach to comprehensively and deeply describe the circumstances or symptoms studied in relation to the conditions for peace annulment applications and the application of these conditions to Decision Number 2/Pdt.Sus-Cancellation of Peace/2023/PN.Niaga Sby Jo. Number 69/Pdt.Sus-PKPU/2020/PN.Niaga Sby. It can be analyzed from the research that the regulations for requesting the annulment of a peace agreement are already established in Law Number 37 of The Year 2004. Article 170, along with Article 171 and Article 291 of the same law, forms the legal basis for the request, specifically addressing issues related to bankruptcy and the postponement of debt payment obligations.